Lifestyle Intervention Among Teachers: Exploring the Feasibility of Making a Maximum of 10,000 Footsteps to Encourage and Promote Daily Physical Activity in the Workplace - Parris, Nicole Camille; Nicholas-Sammy, Euclid (British Journal of Healthcare and Medical Research, 2024)
This study evaluates the impact of a 21-day physical activity challenge on teachers’ engagement in physical activity, their perceptions of its importance, and the overall effects on their health and well-being. A sample of predominantly female teachers participated, reporting a strong interest in physical activity and recognizing its significance for maintaining a healthy lifestyle. The challenge indicated increased physical activity, improved morale, and enhanced interactions among staff. The results demonstrated that many participants felt motivated to maintain regular physical activity post-challenge, emphasizing the program's positive influence on their physical and mental well-being. Many participants (85%) were female, primarily between the ages of 35-54. The study revealed that most teachers (70%) enjoyed physical activity, with 73% participating in regular exercise. Time management was identified as the most significant barrier to daily physical activity (69%). Participants overwhelmingly agreed (90%) that maintaining a healthy lifestyle was important, and many reported positive effects such as improved fitness, motivation, and mental health. Observations during the challenge indicated increased enthusiasm and camaraderie among participants, with many going out of their way to meet daily step goals. Verbatim responses further emphasized the positive influence of the challenge, with teachers expressing increased awareness of their health and a desire to continue engaging in physical activity.